Green and Sustainable Valorization of Bioactive Phenolic Compounds from Pinus By-Products - Ferreira-Santos, Pedro (Molecules, 2020)
In Europe, pine forests are one of the most extended forests formations, making pine residues and by-products an important source of compounds with high industrial interest as well as for bioenergy production. Moreover, the valorization of lumber industry residues is desirable from a circular economy perspective. Different extraction methods and solvents have been used, resulting in extracts with different constituents and consequently with different bioactivities. Recently, emerging and green technologies as ultrasounds, microwaves, supercritical fluids, pressurized liquids, and electric fields have appeared as promising tools for bioactive compounds extraction in alignment with the Green Chemistry principles. Pine extracts have attracted the researchers’ attention because of the positive bioproperties, such as anti-inflammatory, antimicrobial, anti-neurodegenerative, antitumoral, cardioprotective, etc., and potential industrial applications as functional foods, food additives as preservatives, nutraceuticals, pharmaceuticals, and cosmetics. Phenolic compounds are responsible for many of these bioactivities. However, there is not much information in the literature about the individual phenolic compounds of extracts from the pine species. The present review is about the reutilization of residues and by-products from the pine species, using ecofriendly technologies to obtain added-value bioactive compounds for industrial applications.